Exploring EFL learners' perception of Google Forms as an assessment tool in learning English / Muhalida Zia Ibhar and Frinov Feldiko Ibhar - Ibhar, Muhalida Zia; Ibhar, Frinov Feldiko (Universiti Teknologi MARA, 2023)
In this digital era, technology has become an integral part of education, transforming the way students learn and teachers assess their progress. One powerful tool that has gained significant popularity in educational settings is Google Forms. Originally designed as a survey tool, Google Forms has evolved into a versatile platform that can be effectively used for educational assessment purposes. The study highlights the benefits of using Google Forms, such as flexibility, user-friendly interface, variety of question types, immediate feedback, data analysis capabilities, engagement, and time efficiency. However, potential limitations and challenges related to security, technical issues, and technology access are also mentioned. The study aims to provide insights and recommendations for educators and institutions to effectively use Google Forms as an assessment tool and promote successful language learning outcomes for EFL learners. The problem statement addresses the need to further investigate EFL learners' perception, attitudes, experiences, challenges, and contextual factors that may influence their perception of Google Forms. The methodology outlines the use of Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis to examine the relationships and collect data from EFL learners with the sample of about 100 respondents. The findings revealed the effectiveness and usefulness of Google Forms in the EFL context. Overall, this study contributes to the existing knowledge on the use of Google Forms as an assessment tool in English language learning. It underscores the significance of learners' perception and highlights the potential of technology-enhanced assessment tools in promoting effective language learning experiences.